Weed interference with no‐till soyabeans influenced by fine‐scale covariation between soil properties and cover crop performance. (10th October 2018) - Eslami, S V; Davis, A S
Summary: Balancing trade‐offs in conservation agriculture between the conflicting impacts of soil disturbance on crop yield and soil quality is complicated by the need for adequate weed management, especially in production systems with low, or no, reliance upon herbicides. Production of soyabeans no‐till planted into a rolled‐crimped cereal rye cover crop is attracting increasing farmer interest. Experimental work on this approach to date has provided inferences at the field scale and above, helping to identify broad recommendation domains for best management practices. For individual growers, however, fine‐scale information may also be helpful for making in‐field adjustments to refine the system. In a three‐year field study in Illinois, USA, we quantified key associations among no‐till soyabean performance in a rolled rye system and decametre‐scale variation in soil characteristics, cover crop performance and weed growth. Subfield variation in soil properties had both direct and indirect effects on soyabean yield. Local soil potassium limitation was linked to reduced rye height, which in turn indirectly reduced soyabean yields through decreased weed suppression by the cover crop. Slow‐draining field areas that were still moist at the time of cover crop termination were associated with lower soyabean stands, directly reducing yields. Although the subfield characteristics influencing soyabean and cover crop performance may vary from farm to farm, this study highlights potential gains to be realised in this production system from a better understanding of how such properties covary at fine spatial scales and taking steps to create an environment conducive to maximising cover crop establishment and growth.